Pengaruh Suhu Gas-Plastik dan Air-Pendingin Kondensor terhadap Minyak yang Dihasilkan pada Proses Pirolisis Plastik - Rangkuti, Chalilullah; Rijani, Muhamad (MESIN, 2019)
Nowadays, especially in big cities like Jakarta, there are a lot of people's needs every day and produce a huge amount of garbage which reaches 6000 tons dumped to Bantar Gebang landfill area every day and not to mention those which is not collected by scavengers. Of those garbage, 13%-14% of the waste is plastic type. In this study the distillation method is used. By pyrolysis method the plastic is heated and gasified to different temperatures before it goes to the condenser and converted to oil using different cooling water temperatures of the condenser. The results of this study, for 1 kg of plastic processed the optimum temperature of the gasified plastic of 90 oC with cooling water condenser temperature of 15 oC is producing 800 mL of plastic-oil, which is 68% of the weight of the plastic being processed. The plastic-oil produced is close to the type of gasoline.